Royal College of Physicians Intercollegiate Stroke Working Party evidence‐based guidelines for the nutritional support of patients who have had a stroke. Issue 2 (20th November 2013) - Gomes, F.; Hookway, C.; Weekes, C. E.
Abstract Background Stroke affects 15 million people each year worldwide and is one of the world's leading causes of death and physical disability. Stroke can result in a decline in nutritional status and this is associated with increased mortality and poor outcomes. The present work aimed to systematically review key aspects of the nutritional support of stroke patients at risk of malnutrition and to provide evidence‐based guidelines for use in clinical practice. The work was conducted as part of the process to develop the 4th edition of the Royal College of Physicians' (RCP) 'National Clinical Guideline (NCG) for Stroke'. Methods Questions were generated by the search team, together with contributions from members of the Virtual Stroke Group and the RCP Intercollegiate Stroke Working Party Guideline Development Group. Six questions covering several areas of nutritional support after stroke were defined and searches were conducted through to 31 October 2011 using five electronic databases (Embase, Medline, CINAHL, Cochrane Library and Web of Science). All included studies were assessed for quality and risk of bias using the van Tulder criteria for randomised controlled trials (RCTs) and the Quorum criteria for systematic reviews. Results In total, 4215 abstracts were identified, 24 papers were reviewed and 13 systematic reviews and RCTs were included to provide evidence for the nutritional support components of the guidelines. For each question, evidence statements, recommendations and practical considerations were developed. Conclusions This systematic review process has resulted in the development of evidence‐based guidelines for use in clinical practice and has identified areas for further research.